Targeting pre-mRNA splicing in cancers: roles, inhibitors, and therapeutic opportunities - Araki, Shinsuke; Ohori, Momoko; Yugami, Masato (Frontiers in Oncology, 2023)
Accumulating evidence has indicated that mRNA splicing plays critical roles in a variety of physiological processes, including development of multiple diseases. In particular, alternative splicing is profoundly involved in cancer progression through abnormal expression or mutation of splicing factors. Small-molecule splicing modulators have recently attracted considerable attention as a novel class of cancer therapeutics, and several splicing modulators are currently being developed for the treatment of patients with various cancers and are in the clinical trial stage. Novel molecular mechanisms modulating alternative splicing have proven to be effective for treating cancer cells resistant to conventional anticancer drugs. Furthermore, molecular mechanism-based combination strategies and patient stratification strategies for cancer treatment targeting mRNA splicing must be considered for cancer therapy in the future. This review summarizes recent progress in the relationship between druggable splicing-related molecules and cancer, highlights small-molecule splicing modulators, and discusses future perspectives of splicing modulation for personalized and combination therapies in cancer treatment.